A new method for intuitionistic fuzzy multi-objective linear fractional optimization problem and its application in agricultural land allocation problem - Moges, Demmelash Mollalign; Mushi, Allen R.; Wordofa, Berhanu Guta (Elsevier, 2024)
Article published by Elsevier in the Journal of Information Sciences Volume 625, May 2023, Pages 457-475